Complex presentation of Klippel-Feil syndrome with scoliosis and Sprengel’s deformity: a rare case - Tanya; Bains, Sunil S. (International Journal of Contemporary Pediatrics, 2026)
Klippel-Feil syndrome is a rare congenital anomaly. It is characterized by fusion of two or more cervical vertebrae. In this case report, we have presented a rare case of a nine years old male child suffering from Klippel-Feil syndrome associated with congenital scoliosis and sprengel deformity with no other abnormality in accordance with heart, kidneys, and nervous system. As per the literature review very few cases have been reported on this syndrome thus, this case report is a significant contribution to existing literature.